Development of Quality Standards of Tukhm-e-Khatmi (Seeds of Alcea rosea Linn.) - Fahamiya, N.; Aslam, M.; Siddiqui, A.; Asif, M. (Faculty of Indigenous Medicine, University of Colombo, 2013)
Tukhme Khatmi (Alcea rosea Linn.) is an erect....
Keywords: Tukhme Khatmi; HPTLC; Pharmacognostical; Phytochemical